2004
DOI: 10.1002/ar.a.20001
|View full text |Cite
|
Sign up to set email alerts
|

Expression of hypoxia‐inducible, membrane‐bound carbonic anhydrase isozyme XII in mouse tissues

Abstract: Carbonic anhydrase (CA) XII is a membrane-associated enzyme that has been demonstrated to be normally expressed in some human tissues, to be upregulated in some cancers, and to be a hypoxia-inducible gene product. In mouse, CA XII has been recently localized in the kidney. In the present study, we investigated CA XII gene and protein expression in other mouse tissues, with the kidney serving as a positive control for the reagents. The expression of CA XII mRNA was examined using polymerase chain reaction (PCR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 37 publications
3
19
0
Order By: Relevance
“…Although the function of RNASE4 is not established, ANG1 is part of the acute phase response to infection and has potent antibacterial and antimycotic actions (23). Carbonic anhydrase 12 (CAR12) is a member of a family of proteins involved in the maintenance of pH and ion balance (24). The regulation of all of these genes by FXR was confirmed by RTQ-PCR by using WT, CYP27-KO, and FXR-KO mice administered either GW4064 or vehicle (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Although the function of RNASE4 is not established, ANG1 is part of the acute phase response to infection and has potent antibacterial and antimycotic actions (23). Carbonic anhydrase 12 (CAR12) is a member of a family of proteins involved in the maintenance of pH and ion balance (24). The regulation of all of these genes by FXR was confirmed by RTQ-PCR by using WT, CYP27-KO, and FXR-KO mice administered either GW4064 or vehicle (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…It has been reported that CA12 expression is linked to more differentiated, less invasive status of the tumor cells of the human breast cancer tissues (Wykoff et al 2001). Besides, CA12 expression became stronger with increasing age of mouse embryos, indicating developmental regulation of this protein (Halmi et al 2004). Usually, CA12 is distributed in a variety of normal tissues and its expression becomes stronger in tumors originating from those same tissues (Ivanov et al 2001).…”
Section: Discussionmentioning
confidence: 97%
“…Boeuf et al [30] demonstrated that an elevated CA IX expression is a risk factor of cartilage tumor metastasis. CAs IX and XII are particularly important for extracellular pH regulation and electrolyte balance because of the localization of their CA domains on the extracellular surface of cell plasma membranes [28,29]. It is generally accepted that the avascular articular cartilage is hypoxic [31].…”
Section: Discussionmentioning
confidence: 99%
“…CAs IX and XII are expressed in multiple tissues and their expression is regulated by tissue hypoxia [27,28]. As a marker of hypoxia, their expression in cancer tissue is of interest in cancer therapy and prognosis [3,29].…”
Section: Discussionmentioning
confidence: 99%